Pengaruh intra uterine device (IUD) post plasenta terhadap involusi uterus - Istri Utami; Mochammad Anwar; Herlin Fitriana Kurniawati (Universitas Aisyiyah Yogyakarta, 2016)
Abstract: The study is a quantitative in nature with cohort prospectiveapproach. The population of the study was all post-partum mothers atMlati II Primary Health Centre of Sleman. The samples were takenusing accidental sampling technique with 25 respondents in each caseand control groups. The data were analyzed using Chi Square (X2)while the multivariate analysis used multiple logistic regression of riskfactors model. According to the result, p-value is 0,04 in which there isdifference between post-partum period length on post-partum motherswho use Post placental IUD and post-partum mothers who do notuses Post placental IUD.